2016
DOI: 10.1016/j.pse.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying: a systematic review of research, its prevalence and assessment issues in Spanish studies

Abstract: Research on cyberbullying started at the beginning of the 21 st century and the number of studies on the topic is increasing very rapidly. Nevertheless, the criteria used to define the phenomenon and evaluation strategies are still under debate. Therefore, it is still difficult to compare the findings among the studies or to describe their prevalence in different geographic areas or time points. Thus, the current systematic review has been conducted with the objective of describing the studies on the phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
2
36

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 62 publications
6
70
2
36
Order By: Relevance
“…Our results also show that 28.5% of the total sample had experienced victimization and 14.9% had perpetrated aggression. These data fell within the range reported by Modecki et al () and Zych, Ortega‐Ruiz, and Marín‐López (), although it is not exactly transferrable due to the differences in the criteria employed, and because we allowed for more overlapping roles. We suggest that many data from previous studies and reviews (Brochado, Soares, & Fraga, ; Modecki et al, ; Vivolo‐Kantor et al, ; Zych et al, ) could be discussed under this new triangulation perspective, as neither pure victimization nor pure aggression may be as frequent as we thought.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results also show that 28.5% of the total sample had experienced victimization and 14.9% had perpetrated aggression. These data fell within the range reported by Modecki et al () and Zych, Ortega‐Ruiz, and Marín‐López (), although it is not exactly transferrable due to the differences in the criteria employed, and because we allowed for more overlapping roles. We suggest that many data from previous studies and reviews (Brochado, Soares, & Fraga, ; Modecki et al, ; Vivolo‐Kantor et al, ; Zych et al, ) could be discussed under this new triangulation perspective, as neither pure victimization nor pure aggression may be as frequent as we thought.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Modecki, Minchin, Harbaugh, Guerra, and Runions () found an aggression rate of 35% and a victimization rate of 36% in their meta‐analysis. In Spain, Zych, Ortega‐Ruiz, and Marín‐López (), who examined traditional bullying, reported a similar prevalence. None of these studies addresses the role of bystanders.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Bullying roles and transitions among these roles were discovered and analyzed with a novel methodology using LTA analysis. Therefore, children were classified into bullying roles according to the actual response patterns of the participants instead of traditionally used theoretical criteria, overcoming some of the methodological problems related to these theoretically based bullying roles (see Zych et al., ). Our results showed that the actual bullying roles are not as pure as the roles established theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this is not usually done in the case of bullying where roles are usually established based on only one item (e.g., if a participant answers “once a month” to any item about victimization and “never” to all the items on perpetration, he or she is considered a pure victim). This classification might increase error and decrease reliability even further than single item measures (an error on any item would lead to an erroneous classification; see Zych, Ortega‐Ruiz, & Marín‐López, , for further discussion of this topic). Thus, instead of the traditionally used theory‐based classifications of participants into bullying roles, this study used a latent transition analysis (LTA) that allows the classification of participants based on their actual response patterns that arise from all the items on a scale.…”
Section: Stability and Transitions In Bullying Roles: Existing Theorementioning
confidence: 99%